Computational complexity and memory usage for multi-frontal direct solvers used in p finite element analysis - Calo, Victor; Collier, N.; Pardo, D.; Paszynski, M. (2011)
The multi-frontal direct solver is the state of the art for the direct solution of linear systems. This paper provides computational complexity and memory usage estimates for the application of the multi-frontal direct solver algorithm on linear systems resulting from p finite elements. Specifically we provide the estimates for systems resulting from C0 polynomial spaces spanned by B-splines. The structured grid and uniform polynomial order used in isogeometric meshes simplifies the analysis. © 2011 Published by Elsevier Ltd.